2016
DOI: 10.1210/jc.2015-3924
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Internal Circadian System and Circadian Misalignment on Glucose Tolerance in Chronic Shift Workers

Abstract: Internal circadian time affects glucose tolerance in shift workers. Separately, circadian misalignment reduces glucose tolerance in shift workers, providing a mechanism to help explain the increased diabetes risk in shift workers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
139
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 166 publications
(153 citation statements)
references
References 38 publications
9
139
0
5
Order By: Relevance
“…[25] Human circadian rhythms in glucose and insulin sensitivity are optimised towards ingestion of food in daytime, yet shiftwork often necessitates that food is ingested at night when these endogenous metabolic rhythms are not prepared for food. Experimental studies in humans and animals have shown that this metabolic mismatch can disrupt blood glucose and triglyceride rhythmicity, [27] dampen liver transcriptional rhythms, [28] and ultimately lead to compromised pancreatic beta cell function, decreased energy expenditure, leptin resistance, and diabetes. [28] , [29] , [30] These mechanisms might underlie the epidemiological associations between BMI and diabetes and shiftwork that are identified in this study and others, and the effects of shiftwork on circadian rhythms in metabolic function require further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…[25] Human circadian rhythms in glucose and insulin sensitivity are optimised towards ingestion of food in daytime, yet shiftwork often necessitates that food is ingested at night when these endogenous metabolic rhythms are not prepared for food. Experimental studies in humans and animals have shown that this metabolic mismatch can disrupt blood glucose and triglyceride rhythmicity, [27] dampen liver transcriptional rhythms, [28] and ultimately lead to compromised pancreatic beta cell function, decreased energy expenditure, leptin resistance, and diabetes. [28] , [29] , [30] These mechanisms might underlie the epidemiological associations between BMI and diabetes and shiftwork that are identified in this study and others, and the effects of shiftwork on circadian rhythms in metabolic function require further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Because circadian misalignment in the ‘real world’ doesn't happen in the form of 28-hr days under dim light, Morris et al recently conducted a simulated night shift protocol to simulate more realistic conditions. In this study, a rapid 12-hr inversion of the behavioral and environmental (light/dark) cycles decreased postprandial glucose tolerance, possibly by decreasing insulin sensitivity [31], and these adverse metabolic effects were also observed in chronic shift workers who underwent a similar protocol [53]. The above studies, using statistical methods, suggested that the effects of circadian misalignment were at least in part independent of the sleep loss (which is itself a consequence of circadian misalignment) [29, 31, 53].…”
Section: Mechanisms Linking Circadian Disruption and Glucose Metmentioning
confidence: 99%
“…In this study, a rapid 12-hr inversion of the behavioral and environmental (light/dark) cycles decreased postprandial glucose tolerance, possibly by decreasing insulin sensitivity [31], and these adverse metabolic effects were also observed in chronic shift workers who underwent a similar protocol [53]. The above studies, using statistical methods, suggested that the effects of circadian misalignment were at least in part independent of the sleep loss (which is itself a consequence of circadian misalignment) [29, 31, 53]. By keeping the sleep duration identical in both circadian alignment and misalignment groups (by restricting it to the same amount), Leproult et al could show experimentally that circadian misalignment reduced insulin sensitivity independently of sleep loss [45].…”
Section: Mechanisms Linking Circadian Disruption and Glucose Metmentioning
confidence: 99%
“…Another study showed that the evening chronotype was risk of diabetes and metabolic syndromes [16]. In fact, it is well known that night shift work is a risk of incident diabetes [17,18]. Thus, dinner timing is an important issue in the clinical setting.…”
mentioning
confidence: 99%